Das Christentum: Werden im Konflikt: Selbstwahrnehmung für das Gespräch der Religionen - Meckenstock, Günter (De-Gruyter-Studienbuch, 2008)
This textbook presents a profile of Christianity through its main conflicts. It describes the challenges presented by Modernism and the other world religions. It sketches the main thematic areas which have shaped and continue to shape the development of Christianity in its internal and external conflicts. This succinct presentation of the Christian Faith for students offers also a good basis fordiscussion for the dialog between religions. Günter Meckenstock, Christian-Albrechts-Universität zu Kiel.